Inhibition of arginase by CB-1158 blocks myeloid cell-mediated immune suppression in the tumor microenvironment. Issue 1 (19th December 2017) - Steggerda, Susanne M.; Bennett, Mark K.; Chen, Jason; Emberley, Ethan; Huang, Tony; Janes, Julie R.; Li, Weiqun; MacKinnon, Andrew L.; Makkouk, Amani; Marguier, Gisele; Murray, Peter J.; Neou, Silinda; et al.
Abstract : Background: Myeloid cells are an abundant leukocyte in many types of tumors and contribute to immune evasion. Expression of the enzyme arginase 1 (Arg1) is a defining feature of immunosuppressive myeloid cells and leads to depletion of L-arginine, a nutrient required for T cell and natural killer (NK) cell proliferation. Here we use CB-1158, a potent and orally-bioavailable small-molecule inhibitor of arginase, to investigate the role of Arg1 in regulating anti-tumor immunity. Methods: CB-1158 was tested for the ability to block myeloid cell-mediated inhibition of T cell proliferation in vitro, and for tumor growth inhibition in syngeneic mouse models of cancer as a single agent and in combination with other therapies. Tumors from animals treated with CB-1158 were profiled for changes in immune cell subsets, expression of immune-related genes, and cytokines. Human tumor tissue microarrays were probed for Arg1 expression by immunohistochemistry and immunofluorescence. Cancer patient plasma samples were assessed for Arg1 protein and L-arginine by ELISA and mass spectrometry, respectively. Results: CB-1158 blocked myeloid cell-mediated suppression of T cell proliferation in vitro and reduced tumor growth in multiple mouse models of cancer, as a single agent and in combination with checkpoint blockade, adoptive T cell therapy, adoptive NK cell therapy, and the chemotherapy agent gemcitabine. Profiling of the tumor microenvironment revealed that CB-1158 increased tumor-infiltrating CD8 + T cells and NK cells, inflammatory cytokines, and expression of interferon-inducible genes. Patient tumor samples from multiple histologies expressed an abundance of tumor-infiltrating Arg1 + myeloid cells. Plasma samples from cancer patients exhibited elevated Arg1 and reduced L-arginine compared to healthy volunteers. Conclusions: These results demonstrate that Arg1 is a key mediator of immune suppression and that inhibiting Arg1 with CB-1158 shifts the immune landscape toward a pro-inflammatory environment, blunting myeloid cell-mediated immune evasion and reducing tumor growth. Furthermore, our results suggest that arginase blockade by CB-1158 may be an effective therapy in multiple types of cancer and combining CB-1158 with standard-of-care chemotherapy or other immunotherapies may yield improved clinical responses.